Surgical site infections from emergency interventions carried out at a Reference Children Hospital in Uruguay : (January-July 2016) (Archives of Pediatrics of Uruguay, 2020)
Surgical site infections are a global health problem. Little is known regarding these infections in children at local level; therefore, identifying this problem is essential in order to be able to devise the appropriate strategies to decrease its incidence in health.Objective: describe clinical characteristics and surgical procedures carried out in children having emergency intrahospital surgical site infections at the Reference Children Hospital between January 1, 2016 and July 31, 2016.Metodology: observational, descriptive, retrospective study carried out at the Reference Children Hospital with the purpose of studying the prevalence of intrahospital surgical site infections in patients aged 1 month to 14 years old between January 1 and July 31 2016. The data were obtained through a telephone survey and with informed consent. Intrinsic patient variables, such as, age and sex and extrinsic variables, such as type of surgery, surgery time and post-surgical antibiotic treatment and hospital re-admittance were analyzed.Results: 94 patients were contacted out of 414 who had received emergency surgeries and of 19 who had presented surgical infections. The most common clinical presentation was swelling, heat, and blushing (16, 13 and 13) and 9 patients had fever. The most common infection was appendectomy (43 cases). All patients with surgical infections received antibiotic therapy after surgery.Conclusion: eventhough this paper has some methodological constraints, the infection rate was high in this Hospital during the period January-July 2016. Factors such as the surgery time, duration and type were key to this result. It is essential to reinforce the national epidemiological surveillance of these infections for emergency surgeries as well as for sch-eduled ones, in order to devise better strategies to be able to control this problem.
Keywords: Intra hospital infection; Surgical wound infection